The dynamics of ecological sustainability in housing delivery: Developers’ perspectives - Bamgbaded, J. A.; Fung, Evena Shallonia; Moshood, Taofeeq Durojaye; Kamaruddeen, Ahmed Mohammed; Liew, San Chuin (Taylor and Francis Ltd., 2023)
Housing delivery is facing substantial environmental sustainability threats. Consequently, the housing industry is constantly adopting broad-based actions to sustain the environment and make delivery more efficient and risk-averse. Such regulatory models are sometimes targeted at the housing developers’ readiness, the dimensions of market volatility, technology, and the firm's resources. These variables are more profound within an emerging economic context such as Malaysia, and previous research investigating sustainability agenda in housing delivery has neglected their impacts within the housing developer's perspective. This study tested regional-scale hypotheses regarding predictors of ecological sustainability across the state of Sarawak Malaysia. It was hypothesised that the critical dynamics of technology, developer's readiness, resources, regulatory framework, market turbulence, and uncertainty would increase the likelihood of cumulative environmental sustainability in housing delivery. A sample of 221 Housing developers registered under the Sarawak Housing and Real Estate Developers’ Association and allied professionals were sent a self-report online survey instrument, and 144 completed questionnaires were returned, indicating a 65 per cent response rate. Subsequently, SPSS and SmartPLS were used for data analysis. SPSS was used for data screening, while SmartPLS was used to assess the measurement and structural models. Structural equation models show that improved technology, developer's readiness, and regulatory apparatus are the better correlated with environmental sustainability performance.